Designing a High-Lift Configuration for Bell Spanloads - Bodylski, John. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Jason Rife.; Committee: David Berger, and Robert White.; Keywords: Aerospace engineering, Mechanical engineering, and Fluid mechanics.